The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2004
DOI: 10.1191/0960327104ht479oa
|View full text |Cite
|
Sign up to set email alerts
|

Hepatotoxicity induced by antifungal drugs itraconazole and fluconazole in rats: a comparative in vivo study

Abstract: Itraconazole and fluconazole are oral antifungal drugs, which have a wide spectrum antifungal activity and better efficacy than the older drugs. However, both drugs have been associated with hepatotoxicity in susceptible patients. The mechanism of antifungal drug-induced hepatotoxicity is largely unknown. Therefore, the aim of this present study was to investigate and compare the hepatotoxicity induced by these drugs in vivo. Rats were treated intraperitoneally with itraconazole or fluconazole either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 18 publications
(4 reference statements)
3
68
3
Order By: Relevance
“…Itraconazole also inhibits the enzyme activity of CYP3A4 (26). When rats were pretreated with phenobarbital, an inducer of cytochrome P450, hepatotoxicity induced by itraconazole was significantly reduced (27,37). On the other hand, pretreatment of rats with SKF 525A, an inhibitor of cytochrome P450, significantly enhanced itraconazole-induced hepatoxicity (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Itraconazole also inhibits the enzyme activity of CYP3A4 (26). When rats were pretreated with phenobarbital, an inducer of cytochrome P450, hepatotoxicity induced by itraconazole was significantly reduced (27,37). On the other hand, pretreatment of rats with SKF 525A, an inhibitor of cytochrome P450, significantly enhanced itraconazole-induced hepatoxicity (27).…”
Section: Discussionmentioning
confidence: 99%
“…The cells were washed carefully with PBS once, and Calcein-AM (BD Biosciences) solution in PBS (2 mmol/L final concentration) was added. After incubation at 37 C for an additional 30 minutes, the cells were washed with PBS and the fluorescence-labeled HUVEC tubes were observed under the Nikon Eclipse TS100 fluorescence microscope (485-nm excitation and 520-nm emission) at magnification Â100. Each treatment was done in triplicate and the experiments were conducted three times independently.…”
Section: Huvec Tube Formation Assaymentioning
confidence: 99%
“…Melanin is produced in many cells including the Kupffer cells in amphibian livers (Sichel et al 2002). Additionally, hepatotoxic side effects of itraconazole have been reported in mammals (Collazos et al 1995, Somchit et al 2004; therefore, before itraconazole is adopted as a general treatment for larval amphibians, we suggest more research be undertaken to identify any potential side effects of this antifungal agent. …”
Section: Discussionmentioning
confidence: 99%
“…We also found that TCZ injection reduced the level of ALP, which is a biochemical marker for bone and liverbiliary disorders as well as lapidated liver (15,16). Some studies reported that triazoles reduce ALP levels (6,12), while others claimed the opposite (17,18). The reduced level of ALP may be caused by bile duct hyperplasia observed in histopathological examination of our TCZ-treated samples.…”
Section: Resultsmentioning
confidence: 84%